TINJAUAN PELAKSANAAN MUTASI DAN PENEMPATAN KERJA PADA PT HONDA MAKASSAR INDAH - Dwi Setiawati; Sri Hamdyani; Muh Indra Fauzi Ilyas (AkMen JURNAL ILMIAH, 2019)
Review of the Implementation of Movements and Work Placement at PT Honda Makassar Indah. This research was conducted at a Honda car dealership and repair shop at PT. Honda Makassar Indah in Makassar, located on Jl. A.R. Judge No. 125, Suangga, Tallo, Makassar City. Types and sources of data used Qualitative and quantitative data The population taken in this study amounted to 100 employees with a sample of 50 employees. The results of the study concluded that the most influential variable was the work placement variable with a tcount of 6.068> 1.678 while the mutation variable tcount of 2.781> 1.678. Thus that the two variables are jointly or partially changed, then the most influential change in work performance is work placement